Prevalence of Hyperuricemia at Birat Medical College and Teaching Hospital, Biratnagar, Nepal: Prevalence of Hyperuricemia at Birat Medical College and Teaching Hospital, Biratnagar, Nepal - Sinha, Dr. Amar Kumar (International Journal of Pharmaceutical & Biological Archive, 2019)
Serum uric acid (SUA) and the prevalence of hyperuricemia have been increasing both in developing and developed countries over the past decades. Recent studies suggest that hyperuricemia is an independent risk factor for metabolic syndrome, type-2 diabetes, and cardiovascular disease. Although the incidence of gout in Nepalese adults is increasing, epidemiologic studies on hyperuricemia in the general Nepalese population are limited. The aims of this study were to evaluate the prevalence of hyperuricemia at Birat Medical College and Teaching Hospital, Biratnagar, Nepal. A hospital-based retrospective study was conducted from December 2015 to November 2016. A total of 1513 (507 males and 625 females) outpatient department from Birat Medical College Teaching Hospital, Biratnagar, Nepal, were participated in this survey. Total subject was investigated for SUA by uricase/phenol-aminophenazone (PAP) method. SUA concentration of >7 mg/dl in men and >6 mg/dl in women was considered as hyperuricemia. Overall prevalence of hyperuricemia among the total population (1513) was 25.18%. Among hyperuricemia population, the prevalence of men and women was 25.33% and 25.05%, respectively. The prevalence of hyperuricemia was high in young Nepalese adults of age <20 years (39.53% in men and 35.06% in female). Similarly, >60 years age group, hyperuricemia in men and women was 32.85% and 28.88%, respectively. The prevalence of hyperuricemia among <20 years age group was relatively high followed by >60 years age group. There was high prevalence of hyperuricemia among the men compare to women of these populations of Biratnagar, Nepal.